STATINS USE IN THE PERIOPERATIVE PERIOD ACCORDING TO THE EVIDENCE-BASED MEDICINE - V. V. Samoylenko; O. P. Shevchenko; V. I. Burtsev (Рациональная фармакотерапия в кардиологии)
Optimization of pharmacotherapy in the preoperative period is the cornerstone of the risk modification of cardiovascular complications in the perioperative period. Particular attention has recently been focused on statins use. Evidence base of this drugs class use in the perioperative period serves as the basis for the development of clinical guidelines. However, the results of large randomized trials of statins are controversial. Ambiguous interpretations of these trials data has resulted in significant differences in the classes of recommendations and levels of evidence. Analysis of results of the basic clinical trials and the guidelines of international and national medical societies on the use of statins in patients with cardiovascular diseases to reduce the risk of cardiac complications in the perioperative period in planned extracardiac surgery is presented.